Significance of plumage colour for winter survival in the Tawny Owl (Strix aluco): revisiting the camouflage hypothesis. (12th March 2021) - Solonen, Tapio
Abstract : In snowy winters, the survival of Tawny Owls Strix aluco of the grey colour morph is suggested to be better than that of the brown (or red) morph, partly due to their paler plumage, which is presumed to provide better camouflage against predation. If the difference in the susceptibility to predation between the colour morphs is significant, this should probably be reflected in the relation between the number of snow‐covered days (i.e. the length of the winter) and the number and survival of owls of different colour. In a population in southern Finland there were no significant associations between the number of snowy days during winter and the number of breeding Tawny Owls of different colour morphs in the following spring, but the number of owls, in particular red ones, varied inversely with the number of snowy days in the winter of the previous year. The time lag suggests that the number of snow‐covered days (or some related factors) primarily influenced the pre‐breeding survival of young red owls. However, I found no effect of snow days on the proportion of colour morphs, suggesting only small differences in morph‐specific survival under long‐lasting winter conditions.